Singlet fission initiating triplet generations of BODIPY derivatives through $$π $$ π -stacking: a theoretical study - Takao Tsuneda; Tetsuya Taketsugu (Scientific Reports, 2022)
Abstract The role of singlet fission (SF) in the triplet-state generation mechanism of 1,3,5,7-tetramethyl-boron-dipyrromethene derivatives is revealed by exploring the cause for the solvent dependence of the generation rate. Comparing the adsorption energy calculations of solvent molecules, i.e., cyclohexane, chloroform and acetonitrile molecules, to the derivatives with the $$π $$ π -stacking energies of these derivatives surprisingly show that the hierarchy of the solvation energies and $$π $$ π -stacking energies strongly correlates with the experimentally-suggested solvent dependence of the triplet-state generation of these derivatives for five and more adsorbing solvent molecules. Following this finding, the excitation spectra of these derivatives in acetonitrile solvent are explored using the proprietary spin-flip long-range corrected time-dependent density functional theory. It is, consequently, confirmed that the $$π $$ π -stacking activates the second lowest singlet excitation to trigger the spin-allowed transition to the singlet doubly-excited tetraradical (TT) $$_1$$ 1 state, which generates the long-lived quintet (TT) $$_1$$ 1 state causing the SF. However, it is also found that the $$π $$ π -stacking also get a slow intersystem crossing active around the intersections of the lowest singlet excitations with the lowest triplet T $$_1$$ 1 excitations in parallel with the SF due to the charge transfer characters of the lowest singlet excitations. These results suggest that SF initiates the triplet-state generations through near-degenerate low-lying singlet and (TT) excitations with a considerable singlet-triplet energy gap after the $$π $$ π -stacking of chromophores stronger than but not far from the solvation. Since these derivatives are organic photosensitizers, this study proposes that SF should be taken into consideration in developing novel heavy atom-free organic photosensitizers, which will contribute to a variety of research fields such as medical care, photobiology, energy science, and synthetic chemistry.